69 Do high sensitivity troponin assays actually result in a shorter hospital stay in a real world clinical setting?. (5th June 2017) - Singhal, Arvind; Parsons, Iain; Nicol, Ed
Abstract : Background: Hospitals face an immense bed pressure this winter. Admission to hospital for rule-out of MI is common, and early rule-out may expedite patient turnover. Aims: To assess the time to discharge following introduction of high sensitivity troponin I (hsTnI) in comparison to standard Troponin assays. Methods: A prospective cohort study was undertaken over a 3 month period following the introduction of hsTnI (ARCHITECT assay) at Chelsea and Westminster Hospital in London. Troponin assays were taken at presentation and after 3 hours. A positive result was defined as a high baseline troponin (>68 ng/L for males, >30 ng/L for females) or a change of >50% between the two samples with at least one sample above the 99th centile for gender. The assay results were matched to patient demographics, admission and discharge times and discharge diagnoses. All troponin testing other than that performed at admission were excluded. Results were compared against the conventional Troponin I assay (threshold of detection 32 ng/L), with the 12 hour rule-out protocol, using 6 months of data prior to the introduction of the hsTnI assay. Results: hsTnI were requested on 553 patients in the emergency department over a 3 month period (6.1 patients/day), compared with 647 patients who had conventional troponin I testing over a preceding 6 month period (3.6 patients/day). The mean length of hospital stay was 3.83 days in the hsTnI group vs 2.92 days in the conventional troponin group (p=0.04). The median length of stay was 0.82 days in both groups (p=0.09). All patients who had 2 hsTnI requests ended up being admitted to hospital, even if both were undetectable. No patient who had an undetectable 1st troponin had a positive 2nd troponin. Overall 93/553 (17%) hsTnI results were identified as positive, of which 33/553 (6%) had acute coronary syndromes, with 22/553 (4%) undergoing coronary intervention. 19/553 (3%) had positive hsTnI from other cardiac causes 41/553 (7%) had non-cardiac causes. Conclusions: The introduction of hsTnI has not resulted in a shorter length of hospital stay for patients undergoing troponin testing. Troponin testing became more frequent after the introduction of the new assay which may have resulted in extra, unnecessary admissions. Acute coronary syndromes were relatively uncommon. Combining early rule-out algorithms, such as discharging patients whose initial hsTnI measurement is undetectable, and more judicious use of troponin testing, may prevent unnecessary admissions. Conflict of interests: Nil